The Influence of the Community Learning Centre Organizers Perception about Athnic Buginess Traditional Leadership Behavior and Their Achievement Motive on Performance at South Sulawesi - Syamsul Bakhri Gaffar; Rahmawati Syam (Universitas Negeri Makassar, 2023)
The research aimed to find out the influence of the community learning centre organizers traditional leadership behavior and their achievement motive on performance. The method used in this study, was the survey method with the data collecting technique involving questionnaire, achievement motives scale, performance measurement scale, and documentation. The ordinal scaled data have to be converted into interval scale data with using the Successive Interval Method. The result of the analytical test, using through the path analysis, result are obtained, namely: (1) the traditional leadership behavior has a significant correlation with the achievement motive; (2) the traditional leadership behavior has direct influence to the community learning centre organizers performance; (3) the achievement motive has direct influence to the community learning centre organizers performance, and (4) the traditional leadership behavior and achievement motive are comprehensive influences to the community learning centre organizers performance. The result of the analytical test, showed that they are partially related to the elements of the leadership behavior, namely: the lempu (fair), acca/kanawa-nawa (intelegence), warani (courage), and sugi/masempoi (wealthy), (which were) also explicitly influence the community learning centre organizers performance, except the acca/kanawa-nawa (intelegence) element.